USE OF RHODAMINE WT WITH XAD-7 RESIN FOR DETERMINING GROUNDWATER FLOW PATHS - Close M.E.; Stanton G.J.; Pang L. (My University, 2002)
A passive sampling system for use with rhodamine WT (RWT) in groundwater tracing experiments was developed to assist in the characterisation of groundwater flow paths. Amberlite XAD-7 resin was found to be suitable for adsorption of RWT, which can then be extracted using an ethanol/water mix and analysed fluorometrically. Batch and column experiments showed that XAD-7 resin has a high RWT capacity. The adsorption was slightly dependent on pH, but was always above 75% under batch conditions. The resin had a high percentage mass recovery at flow velocities around 1.5 m/day, but this decreased with increasing flow velocities. Desorption of RWT off the resin in water is dependent on the flow velocity of water and the time after the peak RWT has passed. The mass of RWT extracted from the resin bags correlated very well with both the RWT mass flux in the water and the peak concentrations observed in the monitoring wells in a field experiment. The results of resin bags were reproducible in the field with a mean coefficient of variation equal to 16%. This method has been successfully applied to two field situations with different flow velocities to indicate groundwater flow paths.
Keywords: ADSORPTION; FLOW PATHS; GROUNDWATER; RHODAMINE WT; XAD-7 RESIN